On Processing Conditional Sentences Philip J. Tedeschi. - Tedeschi, Philip J. (Distributed by ERIC Clearinghouse, 1975)
Thirty informants were presented with sets of clauses punctuated as in the pattern "S1. If S2. S3" and asked which clause, S1 or S3, the "if" clause modified. Independently, several linguists judged the sentences "S1, if S2" and "S2, if S3" acceptable. Missing intonational clues or improper punctuation, which frequently occurs in advertising, could force a processing grammar to disambiguate the qualification in the above. Semantic data alone prove insufficient for this disambiguation process; anaphoric and temporal relationships will serve to disambiguate in such cases, but are not always present. If Strawson's "Indirectness Condition" is elaborated by examining the types of non-truth-functional relationships leading from the antecedent to the consequent, a hierarchy which predicts the informants' selections is established. This pragmatic hierarchy, causal/pseudo-causal/inductive/inductive and deductive/deductive, would aid the processing of potentially ambiguous clasuses. It is claimed that the same hierarchy could be applied to disambiguate sentences of the forms "S1. If S2. S3." Further, it is claimed that this hierarchy applies within a generative grammar to limit the acceptability of conjoining arbitrary sentences with "if." (Author/TL)